Nutrient intake of healthy and malnourished preschool children in relation to their family environment - Lim, Loline Valero
Four groups of families, namely H, HM, M, and F were studied to determine the relationship between their food consumption practices, socio-economic status, and the incidence of malnutrition among their preschool children. Group H consisted of 17 families with 33 health preschoolers. Group HM consisted of 24 families with 34 healthy and 34 malnourished preschool children. Group M consisted of 28 families with 54 protein-calorie malnourished preschoolers. Group F consisted of 23 families whose 24 malnourished preschoolers were confined at a hospital malward previous to the study; their mothers underwent training in nutrition and child care while they stayed with their children in the hospital. Social, economic and cultural factors related to the food and nutrient intake of the families were identified by means of the interview method. The nutrient intake of families and that of the preschool children specifically, was determined on the basis of a one-day food recall by their mother. The diets of all the families and the preschool children were high in carbohydrates and low in protein and fats. As to the meal pattern, while the average family member had rice, fish and vegetable for either lunch or supper, only 40 percent of the preschoolers had this combination, 20 percent had rice and fish, and the rest had only rice and either vegetables or broth. Rice was the main component of the diets of all types of families and was the main source of calorie and protein especially among the malnourished children. The health preschool children had better intake of all nutrients than the malnourished. The healthy children exceeded the RDA for protein and iron, and met 99, 90 and 78 percent of the RA for niacin, calorie, and vitamin C, respectively. On the other hand, the malnourished met 95 and 81 percent of the RDA for protein and iron, respectively, 79 percent of the recommended level of niacin, 71 percent for calories, and 45 percent for vitamin C. Other nutrients found to be inadequate in the diets of both groups of preschool children were calcium, vitamin A, thiamine and riboflavin which barely reached 50 percent of the RDA. As a result of the uneven food distribution within the family, the nutrient intake of the average preschooler, except for riboflavin, protein and vitamin A, was lower than an average family member. In Group H, however, their intake was comparable while in the other groups the average intake of the preschooler was much lower than that of the average family member. It was also found that a higher percentage of the protein intake of the preschooler was derived from animal sources as compared to the protein intake of the average family member. Among the families with both healthy and malnourished preschooler (Group HM), the healthy children had a better intake of all the nutrients than their malnourished siblings. The nutrient intake of the average family member of this group was similar to the intake of the average family member of Group H. However, the intake of the average preschooler was more like that of the preschooler of Group M. Among the factors found related to food and nutrient intake of the families were socio-economic status, family size and birth order. Families with malnourished preschoolers had lower income per person than those with healthy children. The average diet rating decreased from 77 to 66 percent as the daily available money per person decreased from PHP 1.07 to PHP 0.60. This group of families were found to be less mobile, having resided in the place for a longer period of time. They also had more unemployed family heads and more working mothers that the families with healthy children. Children of working mothers had lower intake of all nutrients except vitamins A and C compared to those with non-working mothers. The intake of calories, protein, vitamin A, thiamine, riboflavin and vitamin C decreased as the family size increased. Incidence and severity of malnutrition was found to be directly related to birth order. Malnourished children were more commonly found among the fourth or latter children. As a result of the nutrition education of the mothers for Group F in the hospital, about 50 percent of the families have learned to prepare special food for the malnourished preschoolers. Yet, calculation of their nutrient intake still showed that the preschool children of this group had the lowest intake of nutrients among the different groups of children studied.